Ultrasound Imaging of the Axillary Nerve and its Role in the Diagnosis of Traumatic Impairment - Gruber, H.; Peer, S.; Gruber, L.; Loescher, W.; Bauer, T.; Loizides, A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: The axillary nerve (AN) is frequently injured during shoulder trauma and imaging is required to define the site and extent of nerve injury. However, the AN has a rather complex course through several soft tissue compartments of the shoulder and axilla. Therefore, imaging of the nerve with MRI and sonography is troublesome. Thus detection and sonographic assessment bases on thorough knowledge of local topography.Materials and Methods: This investigation aimed at defining reliable anatomical landmarks for AN-sonography in 5 volunteers and later validating the proposed sonographic examination protocol in 10 unselected patients.Results: With strict adherence to the proposed examination algorithm, sonography of the AN was feasible in all volunteers and patients. Furthermore, sonographic findings correlated nicely with the golden standard “surgical exploration” concerning severity and topography of neural impairment.Conclusion: Based on our study results we propose our algorithm for AN-sonography as the first-line imaging tool for the assessment of axillary nerve trauma.
Keywords: nervous-peripheral; ultrasound; trauma